Three dimensional analysis of thermal pad made of nanomaterial, nano-silver with differences of thickness by using CFD software, FLUENT - Mazlan Mohamed; Muhamad Iqbal Ahmad; A.M. Mustafa Al Bakri; Huck-Soo Loo; M.S. Abdul Aziz; Abdullah. N.R (2013)
This paper presents the thermal management of electronic components, microprocessor by using three dimensional numerical analysis of heat and fluid flow in computer using CFD Software. 3D model of microprocessors is built using GAMBIT and simulated using FLUENT software. The study was made for four microprocessors arranged in line under different thickness of thermal pad, inlet velocities and package (chip) powers. The results are presented in terms of average junction temperature of each package. It also found that the thickness of thermal pad, (chip) powers and inlet velocities are the most important elements to control and manage the junction temperature. The strength of CFD software in handling heat transfer problems is proved to be excellent.